The Dualism Generosity and miserliness in the dewan Ibn Himyar Al-Hamdani: cultural reading - Alnami, Musaddif Mousa (Journal of Arabic Language Sciences and Literature, 2024)
Viewing the implicit patterns as immanent in the deep structure of the text, this paper examines a binary opposition in the volume of poetry of one of the Mikhlaf Sulaimani poets (A-Uqaili 1990, 7-13; Al-Akwa' 2008-9, 8-18) in the age of successive states; namely, the poet Mohammed ibn Himyar Al-Hamdani (died 651 AH). It adopts a cultural criticism approach in analyzing the opposition in an attempt to discover the implicit pattern that is concealed by aesthetic, literary and rhetorical devices. The pattern can be reached through the culture of panegyric appraisal of the political authority of the poet's age, especially as he was the poet laureate of the Rasulid King Al-Mansour (Ibn Himyar Al-Hmadani 1985, 21-2). The panegyric culture is one of the main contexts in which many semantic divergences between the explicit pattern in the surface structure and the implicit pattern in the deep structure are found. The paper is divided into two sections, theoretical and applied. The theoretical part deals with terms and concepts, while the applied one examines selected excerpts of Hamdani's poetry and reveals that the cultural pattern dominates the poet's subconscious.
Keywords: the implicit patterns; Generosity and miserliness; Ibn himyar al-hmadani; Cultural criticism